REDUCING THE ENERGY CAPACITY OF DIAMOND SPARK GRINDING BY APPLICATION OF SOLID LUBRICANT - Yury GUTSALENKO; Cătălin IANCU; Alexander RUDNEV; Roman STRELCHUK (Fiabilitate şi Durabilitate)
Diamond spark grinding is known for lower thermo-mechanical stress of mass micro-cutting in the processing zone compared to conventional diamond grinding. This made it possible to propose the organization of the process using the minimum lubrication methodology as an alternative to the conventional jet watering of the treatment zone with water-based lubricating and cooling technological agents. On the example of using an equilibrium mixture of stearin and sebacic acid, it is shown that the introduction of a solid lubricant reduces the energy intensity of diamond spark grinding in comparison with its support with conventional jet watering. The main explanation for this is to reduce the tribological and thermo-mechanical load on the cutting grains and the working surface of the grinding wheel as a whole due to the application of solid lubricant directly to the working contact surface of the tool. The results of the performed experiments make it possible to predict thermo-physically and physic-mechanically intensified schemes of defect-free diamond spark grinding of hard alloys and other difficult-to-machine materials, in particular, with increased contact pressures or cutting speeds. The development of oriented material science practical recommendations in this direction involves additional research with control of the physical quality of the treated surface.